PERANCANGAN APLIKASI PENGELOLAAN TRANSAKSI NASABAH UNTUK MENGHITUNG PENDAPATAN KARYAWAN - Monanza, Yegi Candra; Sutresna, Jaka (Journal of Research and Publication Innovation, 2024)
In the current digital era, technological developments are indispensable in all sectors of work. Various positive and negative impacts are of course always balanced depending on us as users in using technology wisely, in this case especially for most companies, where technology can facilitate human activities. One of the implementations of information technology that is very widely applied to companies is information systems, where one of them is a system application that can support work needs, the impact of which is in addition to precision in workmanship, of course very efficient in processing time. There are various kinds of technology to help work, but there are also many companies that have not implemented these technologies into their work systems. One application that is needed in the company is bookkeeping and calculating employee salaries. Research on this application is felt to be very necessary, very very useful and provides convenience for companies so that they can do bookkeeping and salary calculations for their employees quickly. If you look out there, there are indeed many third-party applications that offer the system, but of course at a price that is not cheap, it is a consideration for the company to buy it, hopefully with research and the application of this system can provide answers to all existing problems. With this application, related companies can use it for corporate purposes.